Can the Diagnosis of Recurrent Vulvovaginal Candidosis Be Improved by Use of Vaginal Lavage Samples and Cultures on Chromogenic Agar? - N. Novikova; A. Rodrigues; P.-A. Mårdh (Hindawi Limited, 2002)
Objective: To investigate if introital and vaginal flushing samples inoculated on chromogenic agar could increase the recovery rate and rapid identification of Candida and non-albicans species, as compared to culture of posterior vaginal fornix samples on Sabouraud agar and speciation of isolates by biochemical tests.